Anton Bruckner, Symphony no. 8 - Korstvedt, Benjamin M. (Cambridge music handbooks., 2000)
Anton Bruckner's Eighth Symphony (1890), one of the last of the great Romantic symphonies, is a grandly complex masterpiece. Its critical reception has been fascinatingly contentious. Its music, at once extensive and distilled, directly confronts the problem of the symphony after Beethoven and after Wagner. This book explores this many-faceted work from several angles. It documents the complicated and often misunderstood history of the symphony's composition and revision and offers an accessible guide to its musical design. It demonstrates, by means of a study of well-known recordings, how performance styles have evolved in this century. It also revisits the conventional wisdom about the various versions and editions of the symphony and comes to some provocative new conclusions. --Publisher description.